The Contribution of Parent Lexical Diversity and Grammatical Complexity to Later Language Outcomes in Mandarin-Speaking Children With Cochlear Implants. - Luo, Jianfen; Xu, Lei; Wang, Min; Li, Jinming; Spencer, Linda; Liu, Huei-Mei; Guo, Ling-Yu (Journal of Speech, Language & Hearing Research, 2026)
Purpose: The study examined the relative contribution of parent lexical diversity and grammatical complexity at different time points to subsequent language outcomes in Mandarin-speaking children with cochlear implants (CIs). Method: Participants were 25 Mandarin-speaking children who received cochlear implantation before 30 months of age. At 1 and 2 years after CI activation, we collected language samples that involved the child playing with the parent for 30 min. The parent's number of different words (NDW) and mean length of utterance (MLU) were computed from the free play for each time point. At 3 years after CI activation, we evaluated children's receptive and expressive language outcomes using a standardized language test. Results: Parent NDW and MLU at 1 and 2 years post-CI activation were significantly correlated with children's language scores at 3 years post-CI activation, except that parent MLU at 1 year was not significantly correlated with children's expressive language scores. Regression analyses further revealed that, at 1 year post-CI activation, parent NDW was stronger than parent MLU in accounting for both children's receptive and expressive language scores at 3 years post-CI activation. At 2 years post-CI activation, parent NDW was relatively more important for children's subsequent receptive language scores, whereas parent MLU at 2 years post-CI activation was relatively more important for children's subsequent expressive language s cores. Conclusions: The relative contributions of parent lexical diversity (NDW) and grammatical complexity (MLU) to later language outcomes in Mandarin-speaking children with CIs evolved over time, particularly for expressive language. The emphasis on lexical diversity and grammatical complexity in parental input should change with the child's developmental level.